2001
DOI: 10.1097/00003677-200101000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Stability: From Formal Description to Issues for Performance and Rehabilitation

Abstract: Low back stability: from formal description to issues for performance and rehabilitation. Exerc. Sport Sci. Rev. Vol. 29, No. 1, pp. 26-31, 2001. The concept of stability, together with notions of design and the application of stabilization exercise, is briefly synthesized. The objective is to challenge muscle systems to achieve sufficient functional stability but in a way that spares the spine of excessive exacerbating load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
235
0
31

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(268 citation statements)
references
References 12 publications
2
235
0
31
Order By: Relevance
“…Post hoc analysis ( ) revealed that the horizontal side-support resulted f the 6 exercises tested, the horizontal side-support and the abdominal crunch, when performed with the abdominal drawingin maneuver, resulted in the greatest changes in muscular thickness of both the TrA and IO muscles regardless of age. These results are in agreement with McGill et al's [22][23][24] recommendation that the horizontal side-support be used as a trunk exercise based on its activation of the multiple trunk-stabilizing muscles (quadratus lumborum, IO, and EO muscles), combined with its low-lumbar loading. Although the horizontal side-support was shown to elicit the greatest change in muscle thickness of the TrA and IO, this exercise may prove difficult for patients with shoulder pathology.…”
Section: Exercise Selectionsupporting
confidence: 91%
See 2 more Smart Citations
“…Post hoc analysis ( ) revealed that the horizontal side-support resulted f the 6 exercises tested, the horizontal side-support and the abdominal crunch, when performed with the abdominal drawingin maneuver, resulted in the greatest changes in muscular thickness of both the TrA and IO muscles regardless of age. These results are in agreement with McGill et al's [22][23][24] recommendation that the horizontal side-support be used as a trunk exercise based on its activation of the multiple trunk-stabilizing muscles (quadratus lumborum, IO, and EO muscles), combined with its low-lumbar loading. Although the horizontal side-support was shown to elicit the greatest change in muscle thickness of the TrA and IO, this exercise may prove difficult for patients with shoulder pathology.…”
Section: Exercise Selectionsupporting
confidence: 91%
“…2,8,22,23,40 The abdominal drawing-in maneuver was performed in conjunction with each of the exercises because of its ability to facilitate coactivation of the TrA and multifidus muscles when stabilizing the trunk and its clinical use as a foundational basis for lumbar stabilization exercises. Recently, Teyhen et al 40 found the abdominal drawing-in maneuver to preferentially activate the TrA with minimal changes in the IO.…”
Section: Exercise Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the muscles of the local stabilization system are located near the vertebral column and can delicately regulate segmental movements 18) . The increased tension in these muscles promotes a compression force between each lumbar muscle and enhances stabilization [19][20][21][22] . Stevens et al reported that the IO/RA ratio was very high because of the relatively small activity of RA during unstable supine bridging exercises 14) .…”
Section: Discussionmentioning
confidence: 99%
“…(There are a number of simple explanations of static stability that interested readers can obtain (Crisco and Panjabi, 1990;McGill, 2001;McGill and Cholewicki, 2001)). This type of static analysis yielded a number of important insights including the requirement for stiffness from trunk muscles to maintain spine stability and prevent injury (Bergmark, 1989;Crisco and Panjabi, 1990;Crisco and Panjabi, 1991), the need for orchestrated recruitment (Bergmark, 1989), and the potential for injury under low level loading (Cholewicki and McGill, 1996).…”
Section: Why Is Stability Important In Spine Biomechanics?mentioning
confidence: 99%